Influence of force causing water molecules to flow in computer simulations of water nanoflows - Bytnar, Janusz; Twaróg, Bogusław; Szostek, Kamil; Piróg, Monika (Bulletin of the Polish Academy of Sciences Technical Sciences, 2026)
Understanding liquid behavior in nanoscale channels is essential for designing advanced systems involving nanofluids. The objective of this study was to evaluate the effect of external forcing applied to water molecules flowing through a copper nanochannel on the thermodynamic stability of the system, using molecular dynamics (MD) simulations. The motivation stems from the lack of clear guidelines for selecting forcing parameters that ensure physically consistent flow without introducing artificial phase transitions. Simulations were conducted for three molecular water models (OPC, PPC, TIP4P) and three forcing magnitudes. The temperature evolution and molecular velocity distributions were analyzed. The results demonstrate that excessive forcing leads to nonphysical behavior, such as overheating beyond the boiling point, whereas insufficient forcing may cause cooling below the freezing point. Only intermediate forcing values allow for stable, realistic flow behavior within the liquid phase. Additionally, the choice of molecular water model was shown to significantly affect flow dynamics, highlighting the importance of proper parameter selection in MD studies. These findings provide practical guidelines for reliable nanoscale flow simulations and may support the design of transport structures in nanoscale devices.